Understanding Corpus Linguistics: A Systematic Review of Concepts, Approaches, and Applications - Puput Anggun Maulina; Rury Fadilah Anwar; Juliea Mutiara Insani; Naidelin Indriyani; Nisa Nofianty; Refika Adriani (PARAFRASE : Jurnal Kajian Kebahasaan & Kesastraan, 2026)
This study aims to systematically review the development of corpus linguistics by examining its concepts, methodological trends, applications, and technological advancements. The research addresses the need for a comprehensive synthesis of corpus linguistics studies in the digital era, as previous studies are often limited to specific contexts. The participants of this study consist of 25 selected research articles obtained through a systematic literature review process using the PRISMA framework, involving identification, screening, eligibility, and quality assessment stages from multiple databases. The method employed is a systematic literature review combined with descriptive and thematic analysis, supported by bibliometric analysis to identify research patterns and trends. The findings reveal that corpus linguistics is widely applied in language learning, linguistic analysis, and technology development, with corpus-based approaches dominating practices. The use of authentic language data enhances learning, improves engagement, and supports data-driven analysis. Additionally, technological tools such as corpus analysis software and artificial intelligence play a significant role in increasing the efficiency and accuracy of linguistic analysis. However, challenges remain in terms of corpus literacy, data validity, and access to resources. This study concludes that corpus linguistics contributes significantly to modern linguistic research and highlights the importance of integrating technology and adaptive approaches